Evaluation of the implementation of disposable mask waste management at Faculty of Medicine, Public Health and Nursing (FKKMK), Universitas Gadjah Mada (UGM) - Shandy Boy; Purwanti Sri; Pamungkas Catur; Fadhlun; Tumiat; Rauf Annisa Utami (BIO Web of Conferences, 2024)
The COVID-19 has introduced new habits such as the daily use of masks, which extends to campus environments. This habit poses health risks as masks are considered infectious waste and can facilitate disease transmission, thus requiring attention in terms of management. As a proponent of the Health Promoting University, FK-KMK UGM is expected to lead by example in managing mask waste. The aim of this study is to evaluate the implementation of mask waste management at FK-KMK UGM. This study used descriptive cross-sectional design with a mixed-method approach. Quantitative data were collected by distributing questionnaires to 141 respondents, while the qualitative method was carried out by evaluating using logic model framework to know the input, process, and output from the implementation. About 81.6% of respondents continued to wear masks on campus, with 65.2% citing health reasons. Furthermore, 85.8% reported the absence of proper mask disposal facilities, and 92.9% indicated a need for such facilities. Regarding input, process, and output components, it was found that lacks designated disposal bins and does not separate mask waste from other waste at FK-KMK UGM. The management of disposable mask waste at FK-KMK UGM has not been implemented properly. The campus should provide specialized bins for mask waste and collaborate with the Center for Agricultural Technology Innovation (PIAT) UGM to integrate mask waste treatment.